Improving the perfomance of commercial mapping on the web : proposals for the web site of the French Forest Authority - Vincent Godard (Cybergeo)
In 1999 the Internet was used for the first time as a marketing medium by the ONF (France’s National Forest Office) to sell timber from state- and locally-owned forests. Using a search engine, this site enables visitors to locate items corresponding to their requests (species, available volume,...). The only map proposed by the ONF is a document indicating roughly the felling location. It seemed appropriate to suggest the addition of an atlas allowing sellers to increase the visibility of the products on sale and visitors to rationalize their purchases. Is the result more efficient? A questionnaire is provided for Cybergeo readers.Keywords: geomatics, Internet, wood sale, applied cartography, ONF